â€œSeafood not Slavefoodâ€: Advokasi Aktivisme Transnasional untuk Mengakhiri Praktik Perbudakan Modern di Industri Perikanan Thailand - Maziyah, Roihanatul; Susiatiningsih, Rr. Hermini (Journal of International Relations, 2020)
In 2013, EJF (Environmental Justice Foundation) launched a global campaign named "Seafood not Slavefood," intended to end modern slavery practices in Thai fishing industry. EJF advocacy efforts succeeded in pressuring the Thai government to ratify the Forced Labor Protocol and ILO Work in Fishing Convention. Hence this study aims to shed light on the EJF's strategy in advocating modern slavery plights that occur in the Thai fishing industry. This study attempts to advance transnationalism by analyzing the role of non-state actors in determining state behavior. This study utilizes the concept of transnational advocacy networks from Keck and Sikkink which carried out within qualitative research methods and literature studies as data collection techniques. This research argues that the boomerang pattern has implication in shaping Thailandâ€™s behavior and its policy. In achieving state policy change from targeted actor, EJF used four strategies, mainly information politics, symbolic politics, leverage politics, and accountability politics.